Association of grip strength and related indices with independence of activities of daily living in older adults, investigated by a newly‐developed grip strength measuring device. (April 2014) - Matsui, Yasumoto; Fujita, Remi; Harada, Atsushi; Sakurai, Takashi; Nemoto, Tetsuya; Noda, Nobuo; Toba, Kenji
Abstract : Aim: To investigate the association of grip strength and activities of daily living independence in older adults, using a newly‐developed grip strength measuring device. Methods: Patients who visited the clinic for memory disorders at the National Center for Geriatrics and Gerontology (142 men and 205 women, mean age 74.8 ± 8.8 years) were included in the present study. Their strength during gripping performance is described in detail, and following the indices were calculated: maximum strength (MS), response time (RT), time to MS, time to reach turning point (TP), strength at TP, inclination from start to TP, time from TP to reach MS, inclination from TP to MS and ratio of strength (TP/MS). Barthel Index (BI), total scores and scores of each subclass were used for evaluating activities of daily living independence. MS was compared between the independent and dependent groups. Correlations, using partial Pearson's coefficient adjusted for age, and Mini‐Mental State Examination total score were analyzed between indices and BI by sex, side, and age groups. Results: MS was significantly higher in the independent group. MS and RT were significantly related with BI total and certain subclasses in both hands, TP/MS was significantly related in the right hand of either sex, and strength at TP was significantly related in both hands in women and in the left hand in men. Time to reach TP was particularly correlated in both hands and time from TP to reach MS in the right hand, in men. The correlation of indices varied by sex, hand side and age group, especially in men aged in their 70s, and in women aged less than 70 years and women aged in their 80s. Conclusion: MS was shown to be useful, but some of the newly defined indices, such as RT, strength at TP, and elements regarding before and after TP until reaching MS, were also suggested to be useful.Geriatr Gerontol Int 2014; 14 (Suppl. 2): 77–86.